The effect of passive leg raising on the cross-sectional area of the right internal jugular vein in obese patients undergoing surgery: a prospective observational study - Dongliang Pei; Shuyan Wang; Chenmin Sun; Xiaoqiong Cao; Pei Zhu; Lijun Cao (BMJ Open)
Objectives To observe the association between passive leg raising (PLR) and the cross-sectional area (CSA) of the right internal jugular vein (IJV) in obese patients undergoing elective surgery.Design Prospective observational study with randomised position sequence.Setting Single-centre, tertiary care hospital in Shanghai, China.Participants Forty obese patients (body mass index (BMI) >30 kg/m²) scheduled for elective surgery were enrolled. Inclusion criteria were American Society of Anesthesiologists Physical Status Classification (ASA) physical status II–III and age ≥18 years. Exclusion criteria included history of neck surgery, severe cardiovascular disease, end-stage renal disease, severe infection or sepsis and significant coagulopathy.Observations Patients underwent ultrasound measurements of the right IJV in two positions: supine (S0) and passive leg raise at 40° (PLR40). Each position was maintained for at least 1 min prior to measurement.Primary outcome The primary outcome was to observe whether the CSA of the right IJV differed between the S0 position and passive leg elevation. In post hoc analyses, we examined factors affecting the relative CSA change (CSAγ), including neck circumference, BMI, age, sex, ASA physical status and heart rate as predictors.Results The CSA of the right IJV was significantly larger in the PLR40 position (2.05 cm²) compared to the S0 position (1.67 cm², p=0.003). Linear regression analysis showed a slight positive correlation between neck circumference and the percentage change in CSA (correlation coefficient: 0.066, p<0.05).Conclusion The CSA of the right IJV was significantly larger in the PLR40 position in obese patients undergoing surgery.Trial registration number Chinese Clinical Trial Registry ChiCTR2400080513.